CEMARAN CENDAWAN MISELIA STERIL DAN PENGENDALIANNYA - Ahmad, Riza Zainuddin (BPPT)
The contamination of fungi is an important problem which must be known and controled. Mycelia sterile is one of contaminated fungi which is seldom known and must be studied. Different morphology, reproduction and physiology of this fungi is important to study because of the strategy for its control. The aim of this research is to study mycelium sterile and the procedure for its controll. The observation was conducted on fungi suspected included mycelia sterile for 3 years at IRCVS Mycology laboratory. Isolation, identification and re inoculation in agar medium wasconducted on suspected fungi as mycelia sterile. The results show that 10 fungi are mycelia sterile. From this research result, it can concluded that mycelium sterile is a contaminating fungi and it is assumed that it can be controlled.Keywords: Mycelia sterile, contamination, control.